DIGITAL COMPETENCE OF A TEACHER OF A VOCATIONAL (VOCATION- TECHNICAL) EDUCATION INSTITUTION AS A NECESSARY CONDITION FOR IMPROVING THE QUALITY OF THE EDUCATIONAL PROCESS (Innovative professional education, 2023)
The rapid development of modern society, digital technologies and innovative means of education require future professionals to acquire new professional knowledge and skills, and to revise approaches to the formation of their professional competence. The active use of digital technologies in education contributes to the effectiveness of the educational process at all levels and the formation of professional competencies of future specialists. The formation of competences is inextricably linked with the informatization of education. Informatization of education is one of the main directions of reforming educational institutions, determined by the needs of modern society, in which individual development of personality is the main thing.
Keywords: digitalization, professional education, digital competences, digital technologies, innovativeness